Optical Spectrum CDMA: a new code construction for Double Weight Code Family - Mohammed, A; Saad, N.M; Syed Alwee Aljunid, Syed Junid; Anuar, Mat Safar; Mohamad Khazani, Abdullah (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org